2002
DOI: 10.1080/10426500211728
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Fungicidal Activities of 4H-Imidazolin-4-ones Containing Sulfur Substituent

Abstract: 4H-Imidazolin-4-ones 3 and 4 were synthesized respectively by base catalytic reactions of 4-methylthiophenol or phenthiol with carbodiimides 2, which were obtained via aza-Wittig reaction of iminophosphorane 1 with aromatic isocyanates. 3 and 4 exhibited good fungicidal activity against Pellicularia sasakii.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 4 publications
0
14
0
Order By: Relevance
“…161.2-162.5 • C, 1 H NMR (CDCl 3 , 300 MHz) δ 8.17 (d, 2H, J = 8. 1 Hz,Ph),8H,Ph) (20), 183 (20), 112 (23), 111 (80), 99 (50), 98 (100), 77 (54). Elemental Anal.…”
Section: -(2-(1-ethylpyrrolidine)methylamino)-3-methylthio-15-diphementioning
confidence: 98%
See 1 more Smart Citation
“…161.2-162.5 • C, 1 H NMR (CDCl 3 , 300 MHz) δ 8.17 (d, 2H, J = 8. 1 Hz,Ph),8H,Ph) (20), 183 (20), 112 (23), 111 (80), 99 (50), 98 (100), 77 (54). Elemental Anal.…”
Section: -(2-(1-ethylpyrrolidine)methylamino)-3-methylthio-15-diphementioning
confidence: 98%
“…16 Taylor 17 also reported the preparation of 6-phenylamino-1,5-dihydro-1-methyl-pyrazolo [3,4-d ]pyrimidin-4-one by utilizing o-phosphoranylideneamino pyrazolyl ester to react with isocyanates and amines. As a part of an extension of our studies on tandem aza-Wittig reaction, [18][19][20] we developed a new versatile solution-phase regioselective annulation process to synthesize novel 6-amino-3-alkylthio-1-phenyl-1,5-dihydro-pyrazolo- [3,4-d ]pyrimidin-4-one derivatives 5 and 6 (Scheme 1) and examined their fungicidal activities.…”
Section: Introductionmentioning
confidence: 99%
“…Its regioselectivity was the same as our previous research [16]. And, in our previous research, it was found that various carbodiimides reacted with nucleophiles followed by cyclization in need of excessive catalytic solid potassium carbonate [13][14][15]. In this work, the cyclization of guanidines 4 was carried out in the presence of EtONa.…”
mentioning
confidence: 63%
“…[1][2][3][4][5][6][7] Recently, we became interested in synthesis of imidazolones and quinazolinones, some of them having shown potential fungicidal activities. [8][9][10][11][12] Here we wish to report further the synthesis and fungicidal activity of some new derivatives of 2-benzothiazolylthio-substituted 4H-imidazol-4-ones and 4(3H)-quinazolinones, which were not easily accessible by routine synthetic method. Ph…”
Section: Introductionmentioning
confidence: 99%